Evaluasi Pelaksanaan Program Vaksinasi Covid 19 pada Anak Usia 6-11 Tahun - Julaeha Julaeha; Yuanita Windusari; Rizma Adila Syakurah (Journal of Telenursing (JOTING), 2023)
This study aims to evaluate the implementation of the Covid-19 vaccination program for children aged 6-11 years in Lubuklinggau City in 2022. Methods. Purpose: This study aims to evaluate the implementation of the Covid-19 vaccination program for children aged 6-11 years in Lubuklinggau City in 2022. Results. This study shows that the evaluation of the COVID-19 vaccination program for children aged 6-11 years has been carried out properly and according to procedures. In planning stock requirements carried out by the pharmacy and vaccinators in accordance with the achievement targets. In implementing the SOP for the Covid-19 vaccination service for children aged 6-11 years, it has been carried out from the beginning to the end of the observation. Monitoring and evaluation of services has been carried out by internal and external parties but does not yet have an evaluation checklist sheet Conclusion. The evaluation of the implementation of the COVID-19 vaccination program for children in the city of Lubuklinggau has been carried out well, but there are several things in monitoring and evaluation and supervision that still do not have checklists. Therefore officers or the Health Service can prepare supervision in the form of a checklist sheet. Keywords: Children, Covid 19, Evaluation, Implementation, Age 6-11 Years